Interpolating Gazans' Non-Violence: Responsibilities in the Academy and the Media - Pace, Michelle; Shehada M., Muhammad; Abu Mustafa, Ziad (PARTECIPAZIONE E CONFLITTO, 2021)
Since the creation of Israel in 1948 its strategies of suppressing Palestinian resistance reveal a conscious scheme of slow elimination of the natives. What concerns us in this article is that, in light of all Israel's intentional violence, episodes of Palestinian non-violence do not capture and sustain the world's attention in the way that violent acts do. In order to fill this gap, and conceptually, we draw upon the rich works of Puar and de Sousa Santos, as well as others, to show how Gazans' heterogeneous ontologies and experiences with Israel's settler colonialism have, over the years, shaped a multiplicity of strategies for resistance. Empirically, we draw upon ethnographic observations and interviews conducted with Gazan Great March of Return (GRM) protesters to analyze their strategies of non-violence. We conclude that, in spite of the lack of sustained focus by academics and the media (in general) on the embedded resilience of Palestinians to Israel's settler colonial regime, and in spite of Israel's targeting of resistance itself, Palestinians' resolve remains as alive as ever in pursuit of their right to have rights. Our analysis in turn has implications for how the media and the academy interpolate and write about non-violence.